A Full-Spectrum Correlated K-distribution Based Interpolation Weighted-Sum-of-Gray-Gases model for CO2-H2O-soot mixture. (15th August 2023) - Liu, Guanghai; Zhu, Jinyu; Liu, Yuying; Consalvi, Jean-louis; Liu, Fengshan
Highlights: A FSCK-based interpolation WSGG method is proposed for CO2 -H2 O-soot mixture. This method displays good accuracy in both fuel-air and dry oxy-fuel sooting flames. This method improves the computational efficiency of existing WSGG obviously. Abstract: The Weighted-Sum-of-Gray-Gases (WSGG) method is extensively employed in laboratorial and industrial radiative calculations due to its simplicity and negligible memory requirement. For a CO2 -H2 O-soot mixture, the superposition model is usually applied to obtain the radiative property of participating medium, which leads to a substantial increase in computing resources. To improve the computational efficiency of existing WSGG methods without significantly reducing accuracy, a Full-Spectrum Correlated K-distribution based interpolation WSGG (iWSGG) method is proposed here. In this method, a CO2 -H2 O-soot mixture is represented by 8 gray gases, whose absorption coefficients are obtained by linear interpolation, rather than the superposition method. The accuracy and efficiency of iWSGG are evaluated in 3 1D and 3 2D sooting flames. The results show that iWSGG demonstrates good accuracy as compared to the benchmark line-by-line solution in fuel-oxidizer and dry oxy-fuel sooting flames. The computational time of iWSGG is about 1/12 of that of WSGG with 5, 5, and 4 gray gases representing CO2, H2 O and soot, and 2/5 of that of WSGG with 5 and 4 gray gases representing CO2 -H2 O mixture and soot.